2014
DOI: 10.3892/mmr.2014.2722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of topical chondrocyte-derived extracellular matrix treatment on corneal wound healing, following an alkali burn injury

Abstract: Abstract. Numerous treatments have been used in the management of corneal chemical burns; however, no optimal treatment for corneal chemical burns currently exists. The present study investigated the effects of topical chondrocyte-derived extracellular matrix (CD-ECM) treatment on corneal wound healing, using an alkali burn mouse model. Topical treatment with CD-ECM was shown to reduce corneal opacity following an alkali burn. A histological examination observed the presence of regenerated epithelial cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Corneal insults induced by the alkali burn represent another complex therapeutic challenge for the ophthalmologist since the injury can progress to an severe corneal ulceration, perforation, opacification, and surface curvature alteration culminating in permanent visual impairment (Okada et al, 2014 ). Numerous studies have focused on the control and prevention of this disease progression with a thorough review of the treatment modalities against the alkali insults (Pattamatta et al, 2013 ; Ambrosone et al, 2014 ; Okada et al, 2014 ; Yang et al, 2015 ). Alkali burns are known to destroy not only the epithelium but also the stroma, marked by the presence of large vacuolated structures in the stroma (Zhang et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Corneal insults induced by the alkali burn represent another complex therapeutic challenge for the ophthalmologist since the injury can progress to an severe corneal ulceration, perforation, opacification, and surface curvature alteration culminating in permanent visual impairment (Okada et al, 2014 ). Numerous studies have focused on the control and prevention of this disease progression with a thorough review of the treatment modalities against the alkali insults (Pattamatta et al, 2013 ; Ambrosone et al, 2014 ; Okada et al, 2014 ; Yang et al, 2015 ). Alkali burns are known to destroy not only the epithelium but also the stroma, marked by the presence of large vacuolated structures in the stroma (Zhang et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…These components serves an important role in tissue and organ morphogenesis, and induce the surrounding cells to repair the wounded tissue instead of forming scar tissue 24 , 25 . The ECM also prevents the triggering of immune responses that are associated with inflammation 26 28 . Our previous reports have shown that chondrocyte-derived ECM (CDECM) suppressed corneal neovascularization (NV) and opacity by modulating the inflammatory reaction in alkaline burn animal models 28 , 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The ECM also prevents the triggering of immune responses that are associated with inflammation 26 28 . Our previous reports have shown that chondrocyte-derived ECM (CDECM) suppressed corneal neovascularization (NV) and opacity by modulating the inflammatory reaction in alkaline burn animal models 28 , 29 . Furthermore, we reported that CDECM has anti-angiogenic effects in pterygium mouse and suture-induced corneal NV rabbits 30 , 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on control and prevention of alkali burn as it’s a very common and has severe effects ( Pattamatta et al, 2013 ; Ambrosone et al, 2014 ; Okada et al, 2014 ; Yang et al, 2015 ). Alkali burns can destroy not only the corneal epithelium but also the corneal stroma, by creating large vacuolated structures ( Zhang et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%